Heat transfer and friction in nonuniform wall roughness lattice. (August 2015) - Xiao, Hongguang; Chen, Wenzhen; Yan, Binghuo
Abstract: The heat transfer and friction characteristics in a new lattice with nonuniform wall roughness are simulated using the unsteady Reynolds-averaged Navier–Stokes (URANS) method with the Reynolds stress model (RSM). The applicable test of the turbulent model is made in a rectangular channel with a roughness wall. The roughness element height ( e ) is specified as a constant, and the influence of the relative roughness pitch ( p/e ) is analyzed in this work. This new lattice with nonuniform wall roughness is shown to be propitious for raising the quasi-periodic large-scale vortex structure even though the pattern is not as regular as that in the lattice with a smooth wall. The flow and temperature fields are redistributed for the introduction of roughness elements. The friction factor gradually decreases with the increase of p / e ; however, minimal value of heat transfer is obtained in the lattice with p / e  = 8. The friction factor and heat transfer in the new lattices are 2.64–3.59 and 3.14–3.30 times larger than those in the lattices with smooth walls, respectively. Considering the effects of both flow resistance and heat transfer coefficient, a new lattice with p / e  = 15 is recommended. Highlights: The nonuniform wall roughness lattice (NWRL) with three-dimensional (3D) roughness elements is proposed. The friction and heat transfer in the new lattice were simulated by CFD. The quasi-periodic large-scale vortex structure is enhanced. The friction factor in NWRL is 2.64–3.59 times larger than that in the traditional lattice. The heat transfer coefficient is 3.14–3.30 times larger than that in the traditional lattice.